2015
DOI: 10.1038/srep09801
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Anaerobic Biodegradation Pathway of n-Alkanes in Oil Reservoirs by Detection of Signature Metabolites

Abstract: Anaerobic degradation of alkanes in hydrocarbon-rich environments has been documented and different degradation strategies proposed, of which the most encountered one is fumarate addition mechanism, generating alkylsuccinates as specific biomarkers. However, little is known about the mechanisms of anaerobic degradation of alkanes in oil reservoirs, due to low concentrations of signature metabolites and lack of mass spectral characteristics to allow identification. In this work, we used a multidisciplinary appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…Under anaerobic conditions, there is theoretically minimal biological degradation of nalkanes. However, Bian et al (2015) found that fumarate can act as an electron acceptor for the D r a f t efficient splitting of the C-C bond and subsequent conversion to alkylsuccinates and ultimately to LCOHs or other products. Grossi et al (2008) also found that n-alkanes seem to be degraded in conjunction with the production of fumarate in the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…Under anaerobic conditions, there is theoretically minimal biological degradation of nalkanes. However, Bian et al (2015) found that fumarate can act as an electron acceptor for the D r a f t efficient splitting of the C-C bond and subsequent conversion to alkylsuccinates and ultimately to LCOHs or other products. Grossi et al (2008) also found that n-alkanes seem to be degraded in conjunction with the production of fumarate in the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…Subsurface biodegradation leads to a well-characterized sequence of compound class losses as microbial groups with anaerobic hydrocarbon-degrading enzymes (Head et al 2003;Aitken et al 2004;Bian et al 2015) metabolize hydrocarbons, leading to generation of acidic compounds and loss of hydrocarbons in a characteristic sequence (n-alkanes > monocyclic alkanes > alkyl benzenes > isoprenoid alkanes > alkyl naphthalenes > bicyclic alkanes > steranes > hopanes) (Peters et al 2005). Biodegradation preferentially removes 12 C and 1 H, leaving 13 C-and 2 H-enriched organic compounds (Stahl 1980;Clayton 1991;Odden et al 2002;Jones et al 2008).…”
Section: Other In-reservoir Processesmentioning
confidence: 99%
“…USEARCH software was used to check chimeras of methanogenic 16S rRNA gene sequences using a QIIME-compatible SILVA 119 release SSURef database ("rdp_gold fasta") file as a reference. Then, for mcrA gene sequences, a de novo operational taxonomic unit (OTU) picking method was applied by QIIME at a cutoff value of 0.05 (Caporaso et al, 2010). Representative OTU sequences were aligned and inserted into the mcrA gene ARB project database through the maximum parsimony method without changing the initial tree topology (Angel et al, 2012;Ludwig et al, 2004).…”
Section: Clone Library Construction and Analysismentioning
confidence: 99%
“…After merging paired-end reads from raw sequencing data with FLASH-1.2.8, the fastx toolkit was applied to split merged reads from one run into individual samples according to the primer barcodes (Magoc and Salzberg, 2011). Then, all sequences were split into each library with the name of each sample attached according to the barcode map using the QI-IME command "split_libraries" (Caporaso et al, 2010). The criterion for filtering out underqualified sequences was "-s 15 -k -a 6 -r -l 150 -b 12 -M 5 -e 0".…”
Section: Miseq Sequencing and Qiime-based Analysismentioning
confidence: 99%
See 1 more Smart Citation